Rekonstruksi Program Kelompok Kerja Guru SD/MI Pendidikan Agama Islam di Kecamatan Tambaksari Surabaya - Tolchah, Moch (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2018)
This study aims to describe: the working group program of Islamic religious education teachers in Tambaksari Sub-district of Surabaya City, the mechanism of program implementation, its effectiveness, the supporting and inhibiting factors, the ideal profile construction program according to the board, and the reconstruction of the working group of teachers of religious education of Islam.The approach used is qualitative. The subject is coach, clerk, and cluster coordinator. Data were collected by observation, interview, and documentation. Data were analyzed by Yin model. Result of research: (1) program of working group of Islamic religious education teacher formulated at the beginning of each year through deliberation of board, builder, and cluster representative. Work programs are grouped per field, covering areas of religious dissemination, training and development, fundraising and welfare, and public relations; (2) Mechanism: The coach conducts incidental guidance, the general chairman is responsible for the organization's performance to the members, the field leader and the cluster coordinator are responsible to the chairman; (3) The effectiveness of the implementation teacher working group program of the Islamic teacher education can not be known because the board has not evaluated the results, but seen from the program implementation until September 2017 about 70% of the program can be done. The unfinished program is the commemoration of the great Islamic days of Muharram and the Islamic race commemorate the Prophet's Mawlid, social care to the orphanage, the making of android learning media, Quran literacy training, comparative studies, visiting scholars, peer tutors, joint ventures; (4) Supporting Factors: the willingness of the board and members to advance, the ability and openness of the board, and continuous coaching. Inhibiting factors: minimal funds, solid teacher teaching hours, insufficient infrastructure, and lack of government support; (5) Ideal program of working group of Islamic religious education teachers according to the board includes routine and development programs. Routine programs at least: learning discussions, syllabus formation, semester programs, and lesson plans, curriculum analysis, preparation of evaluation instruments, and consolidation of national examinations. Development programs can be selected for at least three of these activities: research, scientific writing, seminars, workshops, research findings, panel discussions, journal publications, and website development; (6) The main points of reconstruction of the working group of teachers of Islamic religious education include the need for Vision and mission formulation, program objectives, routine and development programs in which each program is formulated to facilitate the evaluation of its success and its implementation schedule.